The effect of rice husks as filler in polymer matrix composites - Hardinnawirda, Kahar (2012)
In this study, rice husks filler polyester composites were produced with rice husks as filler and unsaturated polyester resin as the matrix. Several weight percentages of filler loadings were used; 10 wt%, 15 wt%, 20 wt% and 25 wt% in order to gain insights into the effect of filler content on the mechanical properties and water intake of the composites. The surface fractured of the tensile test specimens were analysed by using Scanning Electron Microscopy. From the findings, the tensile strength of the rice husks filled unsaturated polyester resin composites was found to be decrease as the filler loading increased. However, as it increased to 25 wt%, the strength was slightly increased. As for the young modulus, it showed remarkable increased for 15 wt% of rice husks. Nevertheless, it was decreasing as the rice husks were continually increased up to 25 wt%. Water absorption test was also conducted and the results showed that the composites absorb more water as the weight percentage of rice husks increased, which attributed to the ability of rice husks fillers to absorb water.